The Red and the Green : the Rise and Fall of Collectivized Agriculture in Marxist Regimes. - Pryor, Frederic L. (Princeton legacy library., 2014)
Reorganizing the agricultural sector into large-scale state and collective farms was the most radical transformation of economic institutions implemented by Marxist governments. Frederic Pryor provides perspective on this unique experiment by comparing in a systematic and original fashion the changes in the organization of agriculture in all of the world's Marxist nations. This approach allows not only a clearer understanding of the major lines of agricultural policy and organization in these nations but also a keener insight into the reasons underlying the variations among them. What have.